Socioeconomic Inequalities and Adolescent Fitness: Examining the Association Between SES, BMI, and Physical Fitness in Chandigarh Schools - Dahiya, Rajesh; Thapa, Anshul Singh; Mandeep (International Journal of Research in Interdisciplinary Studies, 2025)
This non-experimental study examined the relationships among socioeconomic status (SES), body mass index (BMI), and physical fitness in senior secondary school students in Chandigarh. The sample consisted of 50 students (25 males and 25 females) selected from five government model senior secondary schools. Data were collected using the AAHPER Physical Fitness Test (1984), the Socio-Economic Status Scale (Aggarwal et al., 2005), and BMI measurements. Product-moment correlation analysis was employed to determine the associations among variables. Results indicated strong correlations between lower body strength and abdominal strength, and significant interrelations among endurance, speed, and agility. Upper body strength showed limited associations, while SES was positively correlated with agility and negatively with abdominal strength. BMI demonstrated a weak negative correlation with upper body strength. These findings underscore the influence of socioeconomic factors on adolescents’ physical fitness and health. The study contributes to evidence-based strategies aimed at improving physical fitness, reducing obesity, and promoting health equity among school-aged populations.